2017
DOI: 10.1097/sla.0000000000002431
|View full text |Cite
|
Sign up to set email alerts
|

The Allosteric Hemoglobin Effector ITPP Inhibits Metastatic Colon Cancer in Mice

Abstract: Restoring oxygen in metastatic colon cancer through ITPP inhibits tumor spread and markedly improves animal survival; an effect that is enhanced through the application of subsequent chemotherapy. These promising novel findings call for a clinical trial on ITPP in patients with colorectal cancer, which is under way.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 32 publications
1
12
0
Order By: Relevance
“…Although this mechanism is attractive, it remains to be seen whether this is a general process that is relevant within the context of CRC. One mechanism in favor of a process linking hypoxia and OPN is provided by a recent paper [123]. It was reported that the restoration of oxygen in metastatic colon cancer through Myo-Inositoltrispyrophosphate (ITPP), a nontoxic, anti-hypoxic molecule that recently has shown significant benefits in experimental cancer models, particularly when combined with standard chemotherapy, inhibits tumor spread and is accompanied by a reduction in malignant serum markers including osteopontin, leading to markedly improved animal survival.…”
Section: Metastasis Formationmentioning
confidence: 99%
“…Although this mechanism is attractive, it remains to be seen whether this is a general process that is relevant within the context of CRC. One mechanism in favor of a process linking hypoxia and OPN is provided by a recent paper [123]. It was reported that the restoration of oxygen in metastatic colon cancer through Myo-Inositoltrispyrophosphate (ITPP), a nontoxic, anti-hypoxic molecule that recently has shown significant benefits in experimental cancer models, particularly when combined with standard chemotherapy, inhibits tumor spread and is accompanied by a reduction in malignant serum markers including osteopontin, leading to markedly improved animal survival.…”
Section: Metastasis Formationmentioning
confidence: 99%
“…The allosteric effector of hemoglobin myo-inositol trispyrophosphate (ITPP) was also shown to locally increase the pO 2 in hypoxic tumors. Even though mixed results exists on the potency of ITPP, which is primarily due to pharmacokinetic aspects, we and others demonstrated its chemo- and radiosensitization capacity in both immunocompromised and immunocompetent tumor models [ 349 – 352 ], For a more comprehensive review on the topic, see [ 348 ].…”
Section: Radiotherapy and Tumor Hypoxiamentioning
confidence: 99%
“…Murine brain (MBrMEC) and bone marrow (MBMMEC)-derived organospecific microvascular endothelial cells (ECs) were established as described 34,[36][37][38] and patented (N1170 3915.6, N13/521715). EL4 (ATCC ® TIB-39™) and EL4-IL2 (ATCC ® TIB-181™) were purchased from ATCC.…”
Section: Cell Lines and Cell Culturementioning
confidence: 99%
“…28,30 This tumour suppressor molecule is a primary regulator of vessel formation and modulates endothelial cell reactivity through the control of immune checkpoints, such as PD-L1, 31 through cross controlling NOTCH4. 32 Myo-inositol-trispyrophosphate is a non-cytotoxic molecule, 28,33 and its tumour-reducing effects 30,34 are suggested to operate through vessel normalization, leading to sustained increases in oxygen partial pressure (pO 2 ) which counteracts hypoxia inside the tumour and inverts its effects. This work shows that ITPP-induced stable normalization induces deep changes in the tumour microenvironment due to hypoxia compensation using two tumour models: melanoma and mammary carcinoma.…”
Section: Introductionmentioning
confidence: 99%